The expression pattern and role of circulating CXCR5+γδ T cells in children with newly diagnosed immune thrombocytopenia - Wang, Jian-Yong; Xin, Yi; Wang, Xiao-Li; Li, Lin-Lin; Li, Ai-Min; Zhang, Xiao-Lu (Frontiers in Pediatrics, 2025)
IntroductionImmune thrombocytopenia (ITP) is the most common bleeding disorder in children. Tfh cells play a crucial role in the pathogenesis of ITP by promoting the production of anti-platelet autoantibodies. Recent studies have shown that CXCR5+γδ T cells not only possess “Tfh-like” cell functions but also can induce Tfh cell differentiation. However, it remains unknown whether CXCR5+γδ T cells are involved in the pathogenesis of ITP. This study aims to investigate the role of CXCR5+γδ T cells in children with newly diagnosed ITP (nITP).MethodsA total of 96 children with nITP and 48 healthy children were enrolled in this study. FCM was used to compare the frequencies of circulating CXCR5+γδ T cells and circulating Tfh cells, as well as the levels of ICOS and CD40l on circulating CXCR5+γδ T cells in both groups. The correlation between circulating CXCR5+γδ T cells and platelets as well as circulating Tfh cells were further analyzed.ResultsCompared with healthy controls, the frequency of circulating CXCR5+γδ T cells was higher in children with nITP, and it was negatively correlated with platelet count. The levels of ICOS and CD40l on circulating CXCR5+γδ T cells in children with nITP were also higher. Children with nITP had a higher frequency of circulating Tfh cells, which was positively correlated with circulating CXCR5+γδ T cells.ConclusionsThe excessive activation and proliferation of CXCR5+γδ T cells may contribute to the pathogenesis of nITP in children. Therefore, it can be used as a target for the immunotherapy of pediatric ITP.